Environmental Noise Analysis during Pile Driving Using a Single Acting Diesel Hammer - Agus Margiantono; Evi Setiawati (Journal of Physics and Its Applications, 2026)
Pile driving activities using diesel hammers are common in large-scale infrastructure development projects. One such project is the construction of a railway track leading to Yogyakarta International Airport (YIA) in Kalidengen Village, where a single acting diesel hammer was employed. This study aims to analyze the environmental noise levels generated by the pile driving process at varying distances from the source. Noise level measurements were conducted at distances of 10 meters, 100 meters, and 150 meters using a calibrated sound level meter. The results show that the noise intensity at 10 meters reached values exceeding 120 dBA, while at 100 meters and 150 meters, the levels decreased significantly but still fluctuated between 50–65 dBA. A comparison was also made between the measured noise levels and theoretical predictions based on spherical spreading loss. The findings indicate a consistent decrease in noise levels with distance, in line with theoretical expectations, although certain deviations were observed due to site-specific conditions such as surface reflections and atmospheric absorption. The average noise levels at 100 meters and 150 meters were found to be close to or slightly above the environmental noise threshold of 55 dBA. This suggests a potential risk of noise disturbance in nearby residential areas. The study concludes that mitigation strategies, such as work time restrictions or temporary barriers, should be considered during pile driving operations in urban or residential settings.